2021
DOI: 10.1242/dev.195404
|View full text |Cite
|
Sign up to set email alerts
|

HoxB genes regulate neuronal delamination in the trunk neural tube by controlling the expression of Lzts1

Abstract: Differential Hox gene expression is central for specification of axial neuronal diversity in the spinal cord. Here, we uncover an additional function of Hox proteins in the developing spinal cord, restricted to B cluster Hox genes. We found that members of the HoxB cluster are expressed in the trunk neural tube of chicken embryo earlier than Hox from the other clusters, with poor antero-posterior axial specificity and with overlapping expression in the intermediate zone (IZ). Gain-of-function experiments of Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…The whole mount in situ hybridization protocol is as described (Wilmerding et al, 2021). Embryos were fixed 2 hours at RT in 4% buffered formaldehyde in PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole mount in situ hybridization protocol is as described (Wilmerding et al, 2021). Embryos were fixed 2 hours at RT in 4% buffered formaldehyde in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Parts of the neural tube expressing GFP were microdissected one day after electroporation and dissociated with trypsin/EDTA 0.25%. A highly enriched population of GFP-expressing cells was isolated by FACS with the use of a dead cell exclusion (DCE)/discrimination dye (DAPI) to eliminate dying cells (Wilmerding et al, 2021). RNA was extracted (RNeasy Mini Kit), reverse transcribed with random primers and cDNA was amplified using a linear amplification system used for building sequencing libraries (done at the GATC).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently analyzed the function and identified target genes of HOXB8 in the developing spinal cord of chicken embryo [12]. In particular, we have demonstrated that the gain of function of HOXB8 in the trunk neural tube of a 2-day-old chicken embryo performed by electroporation of the pCIG-HOXB8 expressing vector (co-expressing nuclear GFP) increases cell death and the amount of the transcript of the gene coding for the tumor suppressor LZTS1 [12]. To test the effect of HOXB8 on ERK oncogenic activity in an in vivo context, we took advantage of a model of ERK-induced neoplasia we developed in the chicken embryo neural tube [27].…”
Section: Hoxb8 Transcription Factor Inhibits Neoplasia Induced By Erk Overactivation In the Chicken Embryo Neural Tubementioning
confidence: 99%
“…Similarly, HOXB8 acts as an oncogene in several cancers including colorectal cancer [10], but is a favorable prognostic marker in renal cancer (Human Protein Atlas) [11]. HOXB8 has also been recently shown to positively control the transcriptional expression of the tumor suppressor LZTS1 [12]. A better understanding of the molecular mechanisms that promote either the oncogenic or tumor suppressor activity of the HOX proteins remains unsolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation